Rules of vengeance - Reich, Christopher, 1961- (Doubleday, 2009)
An ambush on a convoy of limousines turns a romantic rendezvous into a terrorist bloodbath and Doctors Without Borders physician Jonathan Ransom, apprehended by the police and threatened with life imprisonment unless he helps secure his wife Emma's capture, escapes and becomes a spy himself in order to track down Emma and discover the true nature of the conspiracy she appears to be masterminding.